COMMUNITY PERCEPTION OF HALAL TOURISM AND ITS CULTURAL IMPLICATIONS IN LAKE TOBA - Alfadri, Ferri; Lestari, Sry; Pulungan, Ismail (Jurnal EL-RIYASAH, 2025)
The halal tourism program has the potential to positively impact tourist visits, both domestic and international. However, the community surrounding the Lake Toba tourist area has rejected the government's proposed halal tourism initiative. This study aims to explore the perceptions of the Lake Toba community regarding halal tourism, which have led to their resistance to its implementation. Employing a qualitative explanatory approach, the research utilizes Participatory Action Research (PAR) methods combined with a snowball sampling technique. This technique enables continuous data collection through referrals from initial informants to other relevant stakeholders. Data were obtained through observation and in-depth interviews with local residents, tourism practitioners, traditional leaders, government officials, and representatives from the Indonesian Ulema Council (MUI). This approach facilitates a deeper understanding of problem-solving strategies, community needs, and the dynamics of knowledge production and socio-religious change. The findings reveal a perceptual gap between the local community and the government's discourse on halal tourism. Many residents believe that halal tourism may undermine or even eliminate long-standing cultural traditions in the Lake Toba area.